The effect of inclusion turmeric powder on some oxidative characteristics, sex hormones and blood minerals in Libyan Barbary lambs male (Al-Farooq Journal of Sciences, 2026)
This study was conducted at the research unit of the higher institute of Agricultural Technology in Al-fatayh area to determine the effect of inclusion levels of turmeric powder on some oxidative characteristics, sex hormones and blood minerals.The study included 12 Barbary lamps male; 3 months old. The experiment lasted for 3 months, where the lambs were divided into three treatments  and each treatment  contained four replicates, with one lamb in each. The lambs of the first treatment were fed a commercial diet without any additives, while the second and third treatments were fed 1.5% and 3% turmeric powder  the feed, respectively.The results concluded that the MDA level was significantly  (P≤0.05) when turmeric powder was added compared to the control treatment, which achieved the highest value. The results also revealed that inclusion turmeric powder at 3% led to a significant (P≤0.05) increase in the FSH hormone level. However, adding turmeric powder at 1.5% led to a decrease in FSH hormone level compared to the control treatment. While the level of testosterone hormone was significantly increased when turmeric powder was added by 3% compared to the control treatment.
Keywords: turmeric powder .oxidative characteristics. sex hormones, blood minerals